A ratiometric lysosome-targeted fluorescent probe for imaging SO2 based on the coumarin-quinoline-julolidine molecular system. (February 2023) - Liu, Feng-Ting; Han, Wen-Wen; Ren, Hui; Yang, Wan-Jing; Wang, Ruo-Nan; Miao, Jun-Ying; Zhao, Bao-Xiang; Lin, Zhao-Min
Abstract: Similar to nitric oxide (NO) molecule, carbon monoxide (CO) molecule and hydrogen sulfide (H2 S) molecule, sulfur dioxide (SO2 ) is also considered to be another important endogenous signaling molecule. SO2 derivatives are widely used as food antioxidants and antimicrobial agents. However, SO2 is also a toxic environmental pollutant and intake of elevated levels of sulfites can lead to diarrhea, low blood pressure and allergic and asthmatic reactions in susceptible people. The specific physiological effects and transformation processes of SO2 and its derivatives are not well understood due to the limitations of existing detection methods. Therefore, it is an urgent need to develop highly sensitive, high-resolution, real-time in situ assays. Herein, we specifically designed a ratiometric near-infrared fluorescent probe CQT for detecting SO2 derivatives. After the reaction of CQT with HSO3 − /SO3 2−, a gradual decrease in red fluorescence at 662 nm accompanied by an enhanced blue fluorescence at 489 nm, reaching a detection range of 2.8–80 μM. In addition, we found that CQT had high energy transfer efficiency, large Stokes shift and low detection limit, which meant that CQT could sensitively monitor small changes of SO2 concentration in cells and accurately target lysosomes. Graphical abstract: Image 1 Highlights: A novel targeting lysosome NIR fluorescent probe CQT was developed. CQT achieved the dual colorimetric and ratiometric fluorescent strategy. CQT had a large Stokes shift of 251 nm, and 98% energy transfer efficiency. CQT showed high sensitivity and selectivity toward SO2 derivatives. CQT achieved the detection of exogenous and endogenous SO2 derivatives in cells.